Clinical knowledge management using computerized patient record systems is the current infrastructure adequate?. - Lorence, D.P (IEEE Transactions on information technology in biomedicine)
The proliferation of technology in health care, spurred by environmental factors encouraging the adoption of computerized patient records (CPRs), has led to a widely held perception of fully computerized patient information systems as the industry norm. To test the validity of this assumption, using data from a national survey of certified health information managers, we examined the CPR technology adoption rates reported by health information managers, assessing variation across practice settings, regions, and organizational types. Results show that significant nonadoption, and regional variation, exists in the implementation of CPRs. Overall, nonuniform diffusion of computerized health information technology was found, despite national mandates that promote and at times require uniform adoption. A significantly greater number of hospital-based patient records were computerized, compared to clinics and other practice settings. Managers were frequently found to maintain duplicate CPRs and paper-based patient record systems, even after the initial implementation period. Nonuniform regional CPR adoption and redundant paper-based systems were found to be a common practice in medical systems, due in part to cultural factors, mistrust of computerized data, and lack of technology training and knowledge.